2020
DOI: 10.21037/atm-20-6909
|View full text |Cite
|
Sign up to set email alerts
|

Panax notoginseng saponins and their applications in nervous system disorders: a narrative review

Abstract: Panax notoginseng saponins (PNS), also called "sanqi" in Chinese, are the main active ingredients which are extracted from the root of Panax notoginseng (Burk.) F. H. Chen., and they have been traditionally used as a medicine in China for hundreds of years with magical medicinal value. PNS have varied biological functions, such as anti-inflammatory effects, anti-cancer effects, anti-neurotoxicity, and the prevention of diabetes. Nervous system disorders, a spectrum of diseases originating from the nervous syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 72 publications
0
17
0
1
Order By: Relevance
“…Panax notoginseng saponins are also the main effective constituents of Xuesaitong Injection, which is widely used in the treatment of cerebral ischemic stroke and cardiovascular disease in China ( Zhang X. et al, 2015 ). Panax notoginseng saponins have neuroprotective and anti-oxidant activities via reducing the levels of ROS, malondialdehyde and nitric oxide (Model: cisplatin-induced nephrotoxicity model; Dosage: 31.35 mg/kg; Control: vehicle) ( Li et al, 2020a ), while increasing the levels of superoxide dismutase, catalase and glutathione ( Qu et al, 2020 ). Panax notoginseng saponins are also found to be able to modulate gut microbiota and boost the immune system to strengthen the overall health (Model: lincomycin hydrochloride-induced microbial intestinal disorder model; Dosage: 20, 60 mg/kg) ( Sun et al, 2003 ; Song and Hu, 2009 ; Bai et al, 2021 ).…”
Section: Direct and Background Efficacy Of Traditional Chinese Medici...mentioning
confidence: 99%
“…Panax notoginseng saponins are also the main effective constituents of Xuesaitong Injection, which is widely used in the treatment of cerebral ischemic stroke and cardiovascular disease in China ( Zhang X. et al, 2015 ). Panax notoginseng saponins have neuroprotective and anti-oxidant activities via reducing the levels of ROS, malondialdehyde and nitric oxide (Model: cisplatin-induced nephrotoxicity model; Dosage: 31.35 mg/kg; Control: vehicle) ( Li et al, 2020a ), while increasing the levels of superoxide dismutase, catalase and glutathione ( Qu et al, 2020 ). Panax notoginseng saponins are also found to be able to modulate gut microbiota and boost the immune system to strengthen the overall health (Model: lincomycin hydrochloride-induced microbial intestinal disorder model; Dosage: 20, 60 mg/kg) ( Sun et al, 2003 ; Song and Hu, 2009 ; Bai et al, 2021 ).…”
Section: Direct and Background Efficacy Of Traditional Chinese Medici...mentioning
confidence: 99%
“…It possesses various pharmacological activities, such as anticancer, antidiabetic, anti-inflammatory, and antioxidant [ 15 ]. Several studies have found that saponins, the major active ingredients of PN, exerted beneficial effects on AD [ 16 , 17 ]. Li et al [ 18 ] showed that notoginsenoside R 1 had a neuroprotective effect on an APP/PS1 double-transgenic mouse model of AD by upregulating insulin degrading enzyme and suppressing A β accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Each ingredient of CHSC has its own specific functions. For example, Adix Paeoniae Rubra, Ligusticum chuanxiong Hort, Pueraria Radix, P notoginseng, and C tinctorius have already shown the function of anti-inflammation and anti-apoptosis [13][14][15][16][17][18] ; Typhae pollen has demonstrated the ability to attenuate cell injury through various functions against neuronal apoptosis and oxidative stress 19 ; Geosaurus could repress inflammatory responses, inhibit apoptosis, and ameliorate ischemic brain injury 20 ; Siegesbeckiae can reduce brain injury through reducing platelet adhesion and anti-oxidative stress 21 . Due to its complex components, it is difficult to conduct studies on the curative mechanisms of CHSC in previous studies.…”
Section: Introductionmentioning
confidence: 99%